Fabrication, physicochemical and rheological characterisation of a drug-therapeutic oils (doxycycline hyclate-nigella sativa-eugenol) complex emulsion stabilised by lecithin and hydroxypropyl methylcellulose intended for delivery into periodontal pocket - Mohamed, Farahidah; Hamidon, Nurhani Emira; Adina, Anugerah Budipratama; Ardini, Yunita Dewi; Mohd Shafri, Mohd. Affendi (Faculty of Medicine and Health Sciences UPM, 2022)
Introduction: Earlier attempts to stabilise an emulsion, intended for chronic periodontitis treatment which composed of doxycycline hyclate (DH), Nigella sativa oil (NSO), eugenol and several combinations of surfactants failed. To solve the issue, we investigated the ability of lecithin alone and its combination with hydroxypropyl methylcellulose (HPMC) to stabilise the emulsion. Method: Compatibility between DH and other ingredients was first investigated using DSC and ATR-IR. The emulsion was characterised, firstly by preparing three phases: doxycycline/preservatives with or without HPMC (varying quantities), NSO/eugenol and lecithin/surfactants as aqueous, oil and emulsifier phases, respectively. The phases were added and emulsified sequentially at 7000 rpm (10 min) with an overhead stirrer and then at 3000 rpm (15min) using a high-shear mixer. DH assay was performed using validated HPLC method. Results: All ingredients were found to be compatible with doxycycline based on DSC, ATR-IR and supported by acceptable recovery (98.2±2.2 %) of DH from the emulsion. Stable emulsions were produced with particle size of 198.6±8.2 to 279.3±10.7 nm and zeta potential of -48.2±0.4 to -64.0±3.9 mV. The emulsions showed high viscosity (~200 Pa.s) at zero shear rate and exhibited shear-thinning flow upon increased in shear stress yielding viscosity of ~3 Pa.s at 100 s-1 indicating pseudoplastic behaviour suitable for pre-filled syringe packaging intended for delivery into periodontal pocket. Conclusion: Lecithin is an excellent emulsifier that can also impart pseudoplasticity for a complex emulsion constitute of drug and natural oils. This could pave the way for a more complex emulsion formu- lation fusing contemporary and therapeutic oils